Accurate macromolecular crystallographic refinement: incorporation of the linear scaling, semiempirical quantum‐mechanics program DivCon into the PHENIX refinement package. (1st May 2014) - Borbulevych, Oleg Y.; Plumley, Joshua A.; Martin, Roger I.; Merz, Kenneth M.; Westerhoff, Lance M.
<x xml:space="preserve">Abstract</x> Macromolecular crystallographic refinement relies on sometimes dubious stereochemical restraints and rudimentary energy functionals to ensure the correct geometry of the model of the macromolecule and any covalently bound ligand(s). The ligand stereochemical restraint file (CIF) requires a priori understanding of the ligand geometry within the active site, and creation of the CIF is often an error‐prone process owing to the great variety of potential ligand chemistry and structure. Stereochemical restraints have been replaced with more robust functionals through the integration of the linear‐scaling, semiempirical quantum‐mechanics (SE‐QM) program DivCon with the PHENIX X‐ray refinement engine. The PHENIX/DivCon package has been thoroughly validated on a population of 50 protein–ligand Protein Data Bank (PDB) structures with a range of resolutions and chemistry. The PDB structures used for the validation were originally refined utilizing various refinement packages and were published within the past five years. PHENIX/DivCon does not utilize CIF(s), link restraints and other parameters for refinement and hence it does not make as many a priori assumptions about the model. Across the entire population, the method results in reasonable ligand geometries and low ligand strains, even when the original refinement exhibited difficulties, indicating that PHENIX/DivCon is applicable to both single‐structure and high‐throughput crystallography.